Energy Subsidies and their Implications for CO2 Emissions in the Visegrad Group Countries - Molendowski, Edward; Pach‑Gurgul, Agnieszka; Ulbrych, Marta (Comparative Economic Research. Central and Eastern Europe, 2023)
The aim of the article is to present a review of the literature on energy subsidies and the scale and structure of subsidies for energy production in the Visegrad Group countries. It also presents the most important results of an investigation into the relationship and impact of fossil fuel subsidies on CO2 emissions based on a linear regression model. Due to the availability of comparable statistical data, the survey was limited to the period 2015–2020. The analysis does not provide a clear confirmation of the negative impact of the amount of subsidies (from the current or previous year) on the level of CO2 emissions.